2015
DOI: 10.1021/acs.est.5b01360
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic Sink and Biogeochemical Controls on the Accumulation of Polychlorinated Dibenzo-p-dioxins, Dibenzofurans, and Biphenyls in Plankton

Abstract: Polychlorinated dibenzo-p-dioxins and furans (PCDD/Fs) and dioxin-like polychlorinated biphenyls (dl-PCBs) were measured in plankton samples from the Atlantic, Pacific, and Indian Oceans collected during the Malaspina circumnavigation cruise. The concentrations of PCDD/Fs and dl-PCBs in plankton averaged 14 and 240 pg gdw(-1), respectively, but concentrations were highly variable. The global distribution of PCDD/Fs and dl-PCBs was not driven by proximity to continents but significantly correlated with plankton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…This may be ascribed to greater sorption of the more hydrophobic pollutants onto sinking organic carbon. 47,49 A previous study also reported that concentrations of hydrophobic antibiotics in phytoplankton collected from the monitoring sites with higher biomass were lower than those with less biomass due to the biomass dilution effect. 46 Among different antibiotics investigated in this study, the slope of ETM was larger than that of the other antibiotics, suggesting that the effects of phytoplankton biomass on this antibiotic was more prominent.…”
Section: Resultsmentioning
confidence: 92%
“…This may be ascribed to greater sorption of the more hydrophobic pollutants onto sinking organic carbon. 47,49 A previous study also reported that concentrations of hydrophobic antibiotics in phytoplankton collected from the monitoring sites with higher biomass were lower than those with less biomass due to the biomass dilution effect. 46 Among different antibiotics investigated in this study, the slope of ETM was larger than that of the other antibiotics, suggesting that the effects of phytoplankton biomass on this antibiotic was more prominent.…”
Section: Resultsmentioning
confidence: 92%
“…This region is influenced by the Brazil Current, moving water masses originating from off Africa, as part of the South Equatorial Current, southwards along the continent. These water masses only possessed trace amount of POPs, as can be explained by a long residence time enabling biogeochemical processes to deplete compounds either via photoloysis, microbial degradation, or settling as part of the biological pump; , (iii) there was a spike in contaminant concentrations at around 2–5°N, which could represent the northern part of the South Equatorial Current, where some North Atlantic water is already entrained from the North Equatorial Counter Current; (iv) the region between 6 and 11°N, where there was a fairly stable signature of PCBs and HCBs but a lack of PBDEs. Samples taken between 9.7 and 11°N represented water masses that were affected by the Amazon and Orinoco river discharges (given the decrease in salinity).…”
Section: Resultsmentioning
confidence: 99%
“…For several samples, GFFs were analyzed individually, with no compounds detected above MDLs. Prior to extraction, the samples were spiked with 13 C BDEs (28, 47, 100, 99, 154, 153, 183, and 209) for PBDE analysis, PCB 30 and 185 for PCB and OCP analysis, and deuterated PAHs (d 8 -naphthalene, d 10 -phenathrene, d 12 -perylene) for PAH analysis. The concentrated extracts were split into 2 portions: one part of the extract was used for PAHs analysis; another part of the extract was analyzed for PBDEs, indicator PCBs, and OCPs.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This pool is subsequently converted to detritus by phytoplankton aging and zooplankton grazing and digestion, and it is exported to deeper waters by the settling of detritus. It has been shown that the "biological pump" can deplete the concentration of dissolved hydrophobic, persistent chemicals in the surface water and, thus enhance net gaseous deposition from the atmosphere, thus acting as a major sink for both airborne and waterborne POPs [11,14,19]. Experimental evidence has confirmed this aspect [12].…”
Section: Introductionmentioning
confidence: 98%